Research status and prospect of MIMO OTA test methods for 5G terminals - Nan MA; Fei YU; Xiaoli YANG; Xiaodong XU; Zhi ZHANG (Dianxin kexue)
MIMO (multi-input multi-output) OTA (over-the-air) testing is an important method to evaluate the radiation performance of the antenna system, as well as an indispensable step of research ＆ development (R ＆D) and mass production stages.With the advent of the 5G mobile communication system, the introduction of millimeter wave (mmWave) and other new technologies brings new challenges to the traditional MIMO OTA test method, and meanwhile makes OTA testing the only feasible solution for testing future 5G devices.Firstly, the challenges faced by 5G OTA testing was described.Then the applicability of the 4G mobile communication system OTA test method to the 5G OTA performance test was analyzed, and how to extend the low-frequency test method to the mmWave terminal test was studied.Then the current status of 3GPP’s research on MIMO OTA testing was summarized, and the system model, test principle, and performance evaluation indexes of simple-sectored multi-probe anechoic chamber (SS-MPAC) were explained in detail.In addition, smaller setup sizes can still yield reasonable measurement accuracy was verified.Finally, future research trends were prospected.